2013
DOI: 10.1097/mpg.0b013e318287e9d7
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Infrared Spectroscopy Measurements of Splanchnic Tissue Oxygenation During Continuous Versus Intermittent Feeding Method in Preterm Infants

Abstract: Bolus milk feeding increases splanchnic oxygenation in both AGA and SGA infants, whereas continuous feeding does not. Splanchnic oxygenation is higher in AGA than in SGA infants both during bolus and continuous feeding. Continuous enteral feeding could help to limit the risk of hypoxic-ischemic gut damage in preterm infants in critical condition, especially in AGA infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 41 publications
3
28
3
1
Order By: Relevance
“…We used the CSOR for comparison because it is more reliable than splanchnic oxygenation value alone, and has been proposed as marker of abnormal perfusion processes affecting the gastrointestinal tract. 24 Similar to previous studies, [43][44][45] in the present study brain tissue oxygenation remained stable following feedings. This stability is likely attributed to the physiological mechanism of cerebral self-regulation, which maintains cerebral blood flow and oxygen delivery at almost constant levels.…”
Section: Discussionsupporting
confidence: 93%
“…We used the CSOR for comparison because it is more reliable than splanchnic oxygenation value alone, and has been proposed as marker of abnormal perfusion processes affecting the gastrointestinal tract. 24 Similar to previous studies, [43][44][45] in the present study brain tissue oxygenation remained stable following feedings. This stability is likely attributed to the physiological mechanism of cerebral self-regulation, which maintains cerebral blood flow and oxygen delivery at almost constant levels.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, a significant increase in splanchnic oxygenation values, detected by NIRS, has been documented (19,21), consistently with the previously described hemodynamic changes (20). It has been suggested that these variations may be due to the cyclic release of gastrointestinal hormones, such as gastrin, enteroglucagon, and gastric inhibitory peptide, specifically promoted by intermittent bolus feeding (3).…”
Section: Articlessupporting
confidence: 64%
“…In line with this finding, a concomitant increase in splanchnic oxygenation, evaluated by means of NIRS, has been described (19)(20)(21). On the other hand, data about hemodynamic and tissue oxygenation changes related to continuous feeding are scarce, as are data documenting differences between cerebral and splanchnic oxygenation related to continuous feeding.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Some few, of small size and not randomized, studies assessing the impact of different modalities of feeding (bolus versus continuous feeding) on splanchnic oxygenation were performed and they 35 demonstrated that bolus milk feeding induces an increase in splanchnic oxygenation without increasing oxygen blood extraction in both healthy AGA and SGA infants, whereas continuous feeding does not affect gastrointestinal oxygenation. Corvaglia et al 36 reported a significant decrease of splanchnic oxygenation occurring in the second half of continuous feeding and a slight trend toward increase in splanchnic Tissue Oxygenation Index during the final 10 minutes of continuous feeding.…”
Section: Resultsmentioning
confidence: 99%